(untitled) (Intent Research Scientific Journal, 2023)
Taking the teaching of physics to a new level in general secondary education schools of continuing education in today’s informed society is an urgent problem in the field of Education. This article examines the problems of teaching students of general secondary education schools to modern thinking in physics, bringing the teaching to a level that meets the requirements of the postnoclassical educational environment. Also, what modern physics textbooks are like, current physics textbooks in our country are compared with textbooks in developed countries of the world.